Duos Myriapodos notaveis do Brazil: notas myriapodologicas - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1898)
H. Brölemann's work on Brazil's most notable myriapods in 1898.
Keywords: Duos Myriapodos; Brasil; CNPQ::CIENCIAS BIOLOGICAS